2015
DOI: 10.1111/jerd.12167
|View full text |Cite
|
Sign up to set email alerts
|

Color Stability and Surface Roughness of a Laboratory‐Processed Composite Resin as a Function of Mouthrinse

Abstract: Based on the results of this study, patients with resin composite restorations should be warned by the dentists about the discoloration of the restorations and the time period of the mouthrinse that will be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
22

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 35 publications
1
18
0
22
Order By: Relevance
“…But also smoking leads to discolorations on teeth and dental restorations. Intrinsic factors are chemical reactions within the restoration material triggered heredity, age and processing modes of placed restorations [21]. The processes which lead to discoloration of PEEK still remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…But also smoking leads to discolorations on teeth and dental restorations. Intrinsic factors are chemical reactions within the restoration material triggered heredity, age and processing modes of placed restorations [21]. The processes which lead to discoloration of PEEK still remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the literature reviewed, 90 specimens were prepared, so that each sample group had 10 samples [8][9][10][11][12]14,15]. Each specimen had its width at 8 mm and its height at 2 mm, as in the study carried out by Kumari et al in 2015.…”
Section: Discussionmentioning
confidence: 99%
“…The results did not show this protection from staining, just as in 2012, Szesz et al evaluated the possibility of this procedure to minimize or solve the stain caused by beverages, but concluded that there was no effectiveness in the action. In 2013, Falkensammer et al also polished their samples, with no success Other studies used the mark of one week in their evaluations, but with a temporal continuity, as 14 days [5,14], 28 days [17,18], 60 days [9,16] and up to 90 days [7].…”
Section: Discussionmentioning
confidence: 99%
“…Discoloration of dental prostheses and restorations is attributed to either 31,32 : intrinsic factors related to heredity, age, and processing modes of these restorations, 33 or extrinsic factors derived mainly from colorants of food products such as caffeinecontaining beverages or mouth rinses, 34 which in turn adhere on restoration surfaces by 35 : physical and chemical electrostatic forces (van der Waals) and hydrophobic interdigitation.…”
Section: Discussionmentioning
confidence: 99%